WUSCHEL-related homeobox gene PagWOX11/12a responds to drought stress by enhancing root elongation and biomass growth in poplar - Wang, Liu-Qiang (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.